Creating HoPE: Mental Health in Western Australian Maximum Security Prisons - Fleming, Jennifer (2011)
The status of prisoners’ mental health has wide-reaching implications for prison inmates, prison authorities and institutions, and the general community. This paper presents the mental health findings from the 2008 Health of Prisoner Evaluation (HoPE) pilot project in which 146 maximum security prisoners were interviewed across two prisons in Western Australia. Results revealed significant discrepancies across gender and Indigenous status regarding the history and treatment of mental health complaints, use of prescribed psychiatric medication, and experience of psychosocial distress. Illicit drug use and dependency, as well as patterns of self-harm and suicide are also reported. These findings highlight that imprisonment is an opportune time to screen for mental health problems and provide appropriate evidence-based treatment. Although this process may initially increase government costs, it will reduce overall expenditure by improving prisoners’ ability to cope with prison to community transitions, and reduce the high rate of recidivism